irpll Women disempowerment in Baloch and Pashtoon culture of Baluchistan; causes and constraints: Muahmmad Shafiq, Nosheen Rafiq - jan, abdullah (JPL, 2023)
In terms of area, Balochistan constitute the largest province of Pakistan: however, it has the lowest population density in the country. It is considered a backward province that lacks industrialization and infrastructure. Inhabitants are traditional in their culture and rites. Hence, women are marginalized and deprived of their basic right and opportunities. The purpose of the current study is to examine the women empowerment which was constraints by the number of factor.